THE LOCALIZATION OF ACETYLCHOLINESTERASE AT THE AUTONOMIC NEUROMUSCULAR JUNCTION - Robinson, Peter M. (The Rockefeller University Press, 1967)
Acetylcholinesterase has been localized at the autonomic neuromuscular junction in the bladder of the toad (Bufo marinus) by the Karnovsky method. High levels of enzyme activity have been demonstrated in association with the membranes of cholinergic axons and the adjacent membranes of the accompanying Schwann cells. The synaptic vesicles stained in occasional cholinergic axons. After longer incubation times, the membrane of smooth muscle cells close to cholinergic axons also stained. Axons with only moderate acetylcholinesterase activity or with no activity at all were seen in the same bundles as cholinergic axons, but identification of the transmitter in these axons was not possible.